Article 18, Paragraph 3, of the Criminal Procedure Code: Risks and Possibilities - Ardito Vega, Wilfredo (2010)
This paper analyzes the impact of Article 18, paragraph 3 of the new Code of Criminal Procedure, this is developed in relation to Article 149 of the Constitution of Peru. The aforementioned article of the new Criminal Procedure Code states that the penal system can not intervene in those cases where the communal authorities have already exercised their competence. Consequently, it is necessary to develop on which that competence is based. According to article 149 of the Constitution, the communal authorities have jurisdictional functions; in that sense, jurisdictional pluralism is being recognized in a broad sense. Likewise, it is necessary to specify which instances are authorized to perform said functions. The author establishes that these instances are the peasant communities, and within them specifically the communal authorities, and the peasant patrols. It is essential to mention that these functions are optional; that is, the peasant communities can assume them or let the state jurisdiction assume them. In addition, justice can only be administered within the territory of the community; however, this will apply to all people who are in it, whether they are members of the community or not. With respect to material competence, Article 149 does not establish limits; however, it is considered that these should not have jurisdiction over crimes that attempt against the order and interests of the State. Following this line, the Constitution requires respect for fundamental rights Similarly, it establishes that the communal authorities resolve conflicts in accordance with customary law; In addition, it is not specified if there is the possibility of appealing to a state authority. On the other hand, it is necessary to mention that it is essential not to fall into cultural relativism. On the contrary, a coordination between these instances and the state ones what it´s persuades.